Strategi Pemberdayaan Kelompok Tani Hutan (KTH) Dalam Budidaya Lebah Madu di Wilayah KPH Dolago Tanggunu - Soekardjo, Dewi; Ariyanti, Ariyanti; Alam, Andi Sahri (Universitas Tadulako, 2024)
This research aims to empower and identify internal (strengths and weaknesses) and external (opportunities and threats) factors influencing the empowerment of Forest Farmer Groups (FFGs) in honeybee cultivation within the Dolago Tanggung Forest Management Unit, Central Sulawesi. The study was conducted from March to May 2023, involving 45 respondents from 3 FFGs, each comprising 15 members. Qualitative descriptive analysis and SWOT analysis with IFAS and EFAS matrices were employed. The results of the internal and external factor analyses revealed strengths such as training for FFG members and financial assistance, weaknesses including limited FFG members participating in training and difficulties in securing additional funds for maintenance costs. Opportunities encompassed government support and consumer trust in products, while threats comprised weather changes and underutilization of technology for information acquisition. The SWOT analysis placed the study in Quadrant 1, indicating support for an aggressive strategy leveraging strengths to seize opportunities. Strategies suggested involve enhancing relationships among government, FFGs, and partners, boosting honey production and quality, providing regular honeybee cultivation training, utilizing agricultural and information technologies for product marketing, and employing attractive packaging to enhance consumer appeal.